Entre colonialidade[s] e atrocidade[s]: os conflitos territoriais envolvendo os Guarani e Kaiowá e o agronegócio no Estado do Mato Grosso do Sul - Neto, Pedro Bigolin (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation aims to analyze simultaneously the extent to which the territorial conflicts involving the Guarani and Kaiowá and the agribusiness in Mato Grosso do Sul are favorable contexts for the occurrence atrocity crimes and are motivated by the colonial logic. In spite of the legal-formal achievements that point to the recognition of their particularities, the conflicts involving indigenous and land occupants have been aggravated in recent years and have been marked by episodes of extreme violence, notably in Mato Grosso do Sul. The charges against original inhabitants are closely related to the expansion of the land occupation in the region, mainly destined to the monoculture of commodities for export, livestock farming and the industries of sugar and alcohol in the disputed areas. This shows a trend towards the vulnerability of indigenous peoples. To carry out the study, the decolonial perspective and the Framework of Analysis for Atrocity Crimes are presented as ground theory and analytical tool. The first one understands coloniality as constitutive of modernity, as a form of articulating a matrix of power based on the racial hierarchy of the subjects, on the premise that only scientific-modern knowledge is valid and in the inferiorization of non-modern subjectivities. Its permanence to the present day is revealed in the denial of difference and in the quest to eliminate it. The second consists of a document prepared by the UN, whose purpose is to assess the presence of risk factors for atrocity crimes [genocide, crimes against humanity, war crimes and ethnic cleansing]. The work consists in a critical diagnostic study, using bibliographical, legislative, documentary and in locu visits. Territorial elements of the Guarani and Kaiowá peoples and their history are explored in the contact with the karaí [non-Indian] to make explicit the subsistence of a standard of treatment that fails to take into account their cultural particularities and violates national and international laws. As results, several indicators of risk factors for atrocity crimes were found, which consist of: structural discrimination of both public and private initiative, closely related by the agribusiness's political-economic power; deprivations and violations of basic human rights, many of them resulting from the non-regularization of the indigenous land issue; a consistent history of violence, attacks and killings; and the maintenance of an imaginary that inferiorizes indigenous identities by its difference as a strategy of territorial expropriation by the colonial project. In order to overcome these impasses, one must seek answers in the construction of another project, which deals with the difference horizontally and, more immediately, in the demarcation of the ancestral territories of native peoples.
Keywords: Direitos territoriais indígenas; Colonialidade; Modernidade; Crimes de atrocidade; Direitos humanos; Indigenous land rights; Coloniality; Modernity; Atrocity crimes; Human rights; ACCNPQ::Ciências Sociais Aplicadas::Direito